Lean Six Sigma to Reduce Dead Stock at PT Globalindo Intimates - Annandhita Kharisma Putri; Dessy Isfianadewi (Publikasi Indonesia, 2024)
PT Globalindo Intimates is a manufacturing company that produces underwear in the garment sector. In the long run, the accumulation of dead stock in the warehouse becomes an unused company asset, making inventory management ineffective and efficient. This study aims to identify and analyze the factors that cause dead stock materials and provide solutions as an improvement effort in minimizing dead stock in the future to increase the effectiveness and efficiency of PT Globalindo Intimates. The method used is Lean Six Sigma with the DMAIC approach model. The data collection technique is done by observation, interview, and documentation. The results of this study explain that the factors that cause dead stock materials are man, method, environment, and material factors, the causes of which include less careful human resources, lack of understanding related to material handling, less than optimal ordering practices, overstock, damaged / defective goods, poor material storage, and low demand. The improvement efforts that can be made to minimize the occurrence of dead stock in the future so that it is not sustainable include making regulations related to the management and handling of dead stock, managing the inventory management system more effectively, optimizing the application of 5S practices in the warehouse, and conducting training for employees